Pragmatic acts and bilingual audience design: A critical pragmatics analysis of Al Jazeera Arabic and English in the 2026 Iran–Israel–US conflict report - Awliya Rahmi; Mouna Bechlem Bouratoua; Aya Qasim Hasan; Jarot Wahyudi; Ahmed Shbair (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
How a single media institution constructs divergent meanings for two linguistically distinct audiences constitutes a salient question in media studies, particularly where that institution operates at the intersection of Arab and international news. Al Jazeera's Arabic (AJA) and English (AJE) services have attracted considerable scholarly attention as paradigmatic instances of this phenomenon. Previous research has mostly approached both media through framing theory or critical discourse analysis, neglecting the pragmatic mechanisms that direct meaning for different readers. Jacob Mey's critical pragmatics, through its concept of the pragmatic act (pract), affords a more precise entry point into this gap. Employing this framework for comparative analysis, the study examines AJA and AJE coverage of the Iran-Israel-US conflict across five thematic events (February-June 2026). Twenty purposively sampled news articles were coded deductively using Mey's six pract categories: alluding, implying, hinting, voicing, quoting, and echoing. Both AJA and AJE rely most heavily on voicing and implying pract, but diverge in a distinctive secondary pract: AJA layers echoing pract onto this shared foundation, activating Arab collective memory and positioning readers within a solidarity-oriented frame, while AJE layers hinting pract, distributing epistemic authority through formally qualified attribution to cultivate critical consensus among a heterogeneous readership.